THE ANALYSIS OF FACTORS AFFECTING THE VOLUME OF COCONUT EXPORTS IN INDRAGIRI HILIR REGENCY, RIAU PROVINCE - Arnadia, Halisa; Elwamendri, Elwamendri; Fathoni, Zakky (JALOW | Journal of Agribusiness and Local Wisdom, 2024)
This research aims to: 1) Describe the development of coconut export volume, coconut production quantity, coconut export prices to Malaysia, the exchange rate of the rupiah, and Malaysia's per capita GDP from 2000 to 2023. 2) Analyze the influence of Lag2 coconut production quantity, Lag2 coconut export prices to destination countries, the exchange rate of the rupiah, and per capita GDP of destination countries on the volume of coconut exports from Indragiri Hilir Regency from 2000 to 2023. This study utilizes secondary time series data on the volume of coconut exports from Indragiri Hilir, Lag2 coconut production in Indragiri Hilir, Lag2 real coconut export prices, the exchange rate of the rupiah against the US dollar, and Malaysia's per capita GDP over the last 24 years (2000-2023). Data analysis employs descriptive analysis methods and multiple linear regression. The results indicate that the development of coconut export volume from Indragiri Hilir, the quantity of coconut production in Indragiri Hilir, coconut export prices, the exchange rate of the rupiah against the US dollar, and Malaysia's per capita GDP fluctuate and tend to increase. Based on multiple linear regression analysis calculations, there is a positive and significant relationship with Lag2 export price variables, the exchange rate of the rupiah against the US dollar, and Malaysia's per capita GDP. Meanwhile, the variable that has a positive but insignificant effect is Lag2 coconut production in Indragiri Hilir. Keywords: Coconut Export Volume, Production, Export Prices, Exchange Rate, Gross Domestic Product.